PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN BELAJAR HASIL IPA SISWA KELAS IV A SDN 022 JAYAMUKTI DUMAI - Alpusari, Mahmud Alpusari Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract.This researcher is a class action (PTK) is done to improve science learning outcomes A fourth grade students of SDN 022 Jayamukti Dumai Timur by implementing cooperative type models pembelajaan two stay two stray. This study was conducted in May 2014 were carried out with 2 Cycle. This is the subject peelitian A fourth grade students of SDN 022 Jayamukti Dumai Timur totaling 28 students as a source of data. Data collection instruments in this thesis is the observation sheet activities of teachers and students as well as student learning outcomes. Average - The average student learning outcomes previously ie 68,00 of 28 students who completed only 12 students with classical completeness and 42.86% of students who did not complete 16 students with classical completeness 57.14%. In this study presented improving student learning outcomes, achievement of mastery of learning outcomes and increased aktvitas teachers and students. Average - The average student learning outcomes in the first cycle increased by 7.54 points (11.09%) is dar be 75.54 while 68.00 Average - Average student learning outcomes in Cycle II increased by 9.64 points (12.74 %) is from 75.54 into 85.15. The percentage of completeness student learning outcomes in the first cycle increased by 28.57%, from 28 students who completed 20 students moved at 71.43% and the percentage of students do not complete 8 with the percentage of 28.57% while the percentage of completeness student learning outcomes in Cycle II increased by ie 17.86% of the 28 students who completed 25 students with a percentage of 89.29% and an incomplete 3 students with a percentage of 10.71%. Percentage pd teacher activity cycle I and II is 65.00% to 85.00%. The percentage of student activity in the first cycle and the second is 60.00% to 80.00%. Dpat thus be concluded that the hypothesis of this study is to apply cooperative learning model Type Two Stay Stray (TSTS) it can improve the learning outcomes of the fourth grade students of SDN 022Jayamukti Dumai Timur. Keywords: Application of Cooperative Learning Model Type two stay two stray, Science Learning Outcome